Théories et pratiques criminologiques : quand l’organisation mène le jeu - Lemire, Guy (Criminologie, 1986)
The analysis of plea bargaining and diversion shows how criminological theories and principles are shaped by organizational constraints; it also indicates the limits of theories and the need for practical knowledge. The concepts of control and power which are so suspicious to criminologists, should be replaced in an organizational perspective in order to give a new meaning to knowledge and praxis.